Synthesis and Characterization of Novel Surfactants Based on 2‐Hydroxy‐4‐(methylthio)butanoic Acid: 2. Non‐ionic Surfactants. Issue 2 (30th December 2016) - Yu, Guangzhe; Shahrashoob, Zahra; Long, Scott; Liu, Yanjun; da Silva, Ariklenio Alves; Grady, Brian P.; Harwell, Jeff; Arhancet, Graciela
Abstract: This manuscript describes the study of a novel sulfoxide‐based surfactant class, namely the partially oxidized 2‐hydroxy‐4‐(methylthio) butyrate esters. The acid group was reacted with a primary alkyl alcohol or alkyl amine to form esters or amides, respectively, and the sulfide was partially oxidized to the sulfoxide. These sulfoxide surfactants behave as non‐ionic surfactants in response to electrolytes, and have very good water solubility with high cloud temperatures. Surface tensions at the critical micelle concentration as low as 30 mN/m were measured. These surfactants were synergistic with anionic surfactants in the mixed micelle and adsorbed surface monolayer. They exhibited fast surface tension decay, good wetting and foaming performance, and performed equally well as a nonyl‐phenol ethoxylate surfactant in an enzyme‐containing laundry formulation.